Atlas of genetic effects in human microglia transcriptome across brain regions, aging and disease pathologies. (1st February 2022) - Lopes, Katia P; Snijders, Gijsje J. L.; Humphrey, Jack; de Witte, Lot D.; Raj, Towfique
Abstract: Background: Microglia are tissue‐resident macrophages of the central nervous system that are essential for homeostasis, immune response, neurogenesis, and neuronal plasticity. Genetic studies have strongly implicated microglial dysfunction in multiple neurodegenerative diseases. However, investigating genetically‐driven changes in gene expression in microglia has been limited by lack of access to these cells from the number of subjects required to perform well‐powered genomic analysis. Method: Here we describe the transcriptome analysis of 255 primary human CD11b+ microglia samples isolated at autopsy from multiple brain regions of 100 human subjects with neurodegenerative and neuropsychiatric disorders. We performed systematic analyses to investigate various aspects of microglial heterogeneities including brain region, age, sex, and disease. By intersecting transcriptomics and genetics, we performed expression and splicing QTL analyses and by combining microglia from four different brain regions using a multivariate meta‐analysis method (mashR). Result: We observed widespread transcriptome variation associated with microglia, suggesting that these genes may play important role in diversified responses to pathological stimuli of microglia at different locations. We also observed 1, 693 genes (FDR < 0.05) whose expression is associated with age including many genes in Alzheimer's (AD) ( MS4A6A, FCER1G, and CR1 ) or Parkinson's disease (PD) ( BST1 and FCGR2A ) GWAS loci. We identified 3, 611 eQTLs (mashR local false sign rate < 0.05), of which 50% (1, 791) show region‐specific effects. We identified over 300 eQTLs that colocalize with a known risk locus for a neurodegenerative or neuropsychiatric disease, nearly half of which are not found in prefrontal cortex or in peripheral monocytes. We prioritized 7 and 13 putative causal genes for AD and PD, respectively, many of which are novel genes ( ITGAX, USP6NL, TSPOAP1, P2RY12, FCGR2C, and FGF20 ). Fine‐mapping of these colocalized loci with CNS chromatin accessibility (ATAC‐seq) and histone modification (H3K27ac) data nominates candidate causal variants that are within microglia‐specific enhancers and are likely to modify disease susceptibility by regulating gene expression and/or splicing in microglia. Conclusion: In summary, we have built the most comprehensive catalog to date of genetic effects on the microglia transcriptome and propose molecular mechanisms of action of candidate functional variants in several neurological and neuropsychiatric diseases.